Bifunctional electrocatalysts of MOF-derived Co–N/C on bamboo-like MnO nanowires for high-performance liquid- and solid-state Zn–air batteries. Issue 20 (14th May 2018) - Chen, Ya-Nan; Guo, Yibo; Cui, Huijuan; Xie, Zhaojun; Zhang, Xin; Wei, Jinping; Zhou, Zhen
Abstract : MnO@Co–N/C composites were fabricated with excellent bifunctional catalytic activity and outstanding performance for both liquid- and solid-state Zn–air batteries. The excellent electrocatalytic activities are attributed to the unique 1D nanowire structure with abundant Co–N x active sites and a high specific surface area. Abstract : Exploration of cost-effective electrocatalysts that could replace noble metals to promote the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) holds great potential for large-scale applications in energy storage devices such as metal–air batteries. Metal–organic frameworks (MOFs) provide a new route to design highly active catalysts owing to their adjustable composition, morphology and surface area. Herein, a highly efficient bifunctional catalyst was fabricated by forming an interconnected and conducting Co–N/C framework on bamboo-like hollow MnO nanowires. The hybrid demonstrates prominent ORR/OER activity and promising potential in rechargeable Zn–air batteries. Especially, when assembled into solid-state Zn–air batteries, high open-circuit potential and stable discharge–charge cycling platforms were achieved. The outstanding performances stem from the synergistic effect of the two composites in one-dimensional nanowires, facilitating the convenient and sustainable diffusion of electrolytes to active sites. This work provides a new guideline to optimize MOF-derived materials as substitutes for Pt/C and RuO2 noble-metal catalysts for air cathodes in both liquid- and solid-state Zn–air batteries.